Acne and hidradenitis suppurativa. (30th January 2018) - Pink, A.; Anzengruber, F.; Navarini, A.A.
Summary: Acne and hidradenitis suppurativa (HS) both centre on hair follicles. They often occur together as part of the acne tetrad, but are found in distinct localizations. Acne is primarily defined by the presence of comedones and inflammatory lesions. However, in HS the intertriginous localization and chronicity play equally important roles for the diagnosis to the inflammatory lesions. Genetics, bacteria, environmental factors and innate inflammation have all been found to play a role in acne and/or HS. Surprisingly, there is little overlap between the findings so far. The genetics of acne and HS are distinct, bacteria have not been shown convincingly to play a role in HS, and the important risk factors obesity and smoking in HS cannot be easily translated to acne. The one driving factor central to both diseases is innate inflammation, most strikingly involving interleukin‐1. Hence the interleukin‐1 family, as already shown in autoinflammatory conditions associated with acne, could represent attractive treatment targets. Abstract : What's already known about this topic? Acne and hidradenitis suppurativa often occur together and have a related pathogenesis. The innate immune system is involved in both conditions. What does this study add? Hidradenitis suppurativa has no seborrhoea and the role of bacteria is not clear. There may be no association of acne and high body mass index. Both conditions show involvement of interleukin‐1, which could be a rationale for treatment.